Student perseptions' towards listening strategies in online listening class - Dhanie hid dayat (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: Many academic institutions has implemented online learning to ensure the spread of Covid-19 pandemic caused by learning activities. However, not all learning strategies in face to face learning is compatible to be used in online learning. In this case, it is necessary to utilize suitable learning methods and strategies that suitable for online learning. Listening skills is considered as difficult skill to learn in online learning, thus, the researcher aims to study students’ perception towards online listening and learning strategies used in online listening class. This study applied qualitative research method with Likert scale questionnaire as instrument. The study involves 72 participants from third semester students of English department at University of Islam Malang. The data was collected online via of google form and analyzed using Microsoft Excel to measure the perception percentage and listening strategies utilized by students in online listening class. The result shows that most of the students disagreed with many aspects of online listening such as material, assignment, time management, facility, and learning media online listening class. The participants disagreed with all aspects except for learning media and platforms. In terms of to learning strategies, there are more students who are using cognitive than metacognitive strategies. However, the mean score indicates that the students utilize more meta-cognitive strategies than cognitive strategies. For the next research it is suggested to conduct more about listening strategies by measuring the effectiveness of using metacognitive and cognitive strategie